Public space in the Soviet city: A spatial perspective on mass protests in Minsk - Hansen, Arve (Nordlit, 2017)
In many capitals, the central public square is the place where people go en masse when they wish to voice their discontent. The squares used for such collective actions are diverse. Each square has its unique combination of symbols and history; they are used in different ways by the public; and they often have distinct physical characteristics. Yet, in social sciences, when determining what makes collective actions successful, space is often overlooked. In this article, I present an approach for analysing public space in relation to mass protests. I then apply this approach to the Belarusian capital Minsk, where virtually no protests have been successful during the post-Soviet period. In what ways are mass protests in Minsk affected by the perceived (symbolic), social and physical elements of the city’s public spaces? I examine the centre of Minsk in general, and analyse two central squares in particular. The article is based mainly on qualitative, semi-structured interviews with protesters, observers and opposition leaders; research literature; and on my own fieldwork and experiences from living in Minsk. I conclude that space is contributing to the difficulties facing the Belarusian opposition in several ways. 1) The perceived elements of Minsk and the two main squares do not have a preferable symbolic value to the opposition. 2) The social elements of the city show that the political centre is avoided by the public, thus making protests less noticeable. 3) This latter point is important, given that the physical elements of the squares makes policing particularly easy and swift. The physical elements of the squares also limit the protesters’ communication, movement and flexibility. I argue that a spatial perspective should be included in research on collective actions.